Determination Of Flow Resistance Coefficient Using Multiple Linear Regression And Genetic Expression Programming - Abdul Ghaffar, Ahmad Bakri (2019)
The use of the accurate value of the roughness coefficient for flow resistance in the open channel is a necessity in computation. The engineers have used a number of flow resistance equations involving grain roughness, form roughness and a combination of both. However, Manning’s equation has been widely used internationally for predicting roughness values in natural channels. In river engineering, Manning’s roughness coefficient, n, has been used widely in river hydraulic models. The procedure for selecting n is subjective and requires judgment and skill that is developed primarily through experience apart from knowing the factors which affect the values of n. Since flow and boundary roughness vary with existing river conditions, a model of some form must be developed to evaluate n for rivers in Malaysia. This research has been carried out on four rivers namely the river basins of Kinta River, Langat River, Muda River, and Kurau River. A total of 501 data have been collected at the four-river basin. Assessment of the existing equations i.e. Strickler, Limerinos, Bruschin, Griffith, Bray, Jarrett, Julien, and Ab. Ghani was carried out. Based on the evaluation of the selected equations, Jarret (1984) and Ab Ghani et al. (2007) equation are recommended to predict flow discharge for the sandy rivers such as Kinta River and Langat River. For gravel rivers such as Muda River and Kurau River, Jarret (1984), Bruschin (1985) and Limerinos (1970) equation are recommended to predict flow discharge. The development of new equations was carried out in the present study using Multiple Linear Regression (MLR) and Genetic. Expression Programming (GEP). The MLR-based equation (Equation 4.4) is recommended while GEP-based equation (Equation 4.6) is greatly recommended. The development of flow rating curve for the rivers in the present study (Figures 4.16 to 4.19) validate the applicability of Equations 4.4 and 4.6 in calculating the flow discharge which can be used to predict low and high flows for rivers in Malaysia.